Hubungan Antara Pengungkapan-Diri dan Kepuasan Pernikahan dengan Dimediasi oleh Intimasi - Arif Romdhon; Hepy Wahyuningsih (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
The present study was aimed to examine the relationship between self-disclosure and marital satisfaction, and whether the relation between self-disclosure and marital satisfaction meditated by intimacy. The participants of study involved 110 individual marriedpeoples in Cilegon, Banten. As predicted, the result showed that self-disclosure was positively related to marital satisfaction. Furthermore, the result also showed that intimacy was mediator the relationship between selfdisclosure and marital satisfaction. Implications and directions forfuture research were discussed.Keyword: Self-disclosure, intimacy, Marital Satisfaction.